IMPLEMENTATION OF THE PROGRAM OF ADDITIONAL FEEDING FOR STUNTING TODDLER IN PENGODUA VILLAGE, EAST ROTE DISTRICT, ROTE NDAO DISTRICT - Elsi Angelia Likan; Jacob Wadu; Adriana R. Fallo; Yani H. Seran (PT. Radja Intercontinental Publishing, 2026)
Stunting remains a nutritional problem that requires addressing through various interventions, one of which is the Supplementary Feeding Program (PMT). The success of the program is determined not only by the provision of supplementary food, but also by the quality of program implementation at each stage. This study aims to analyze the implementation of the Supplementary Feeding Program (PMT) for stunted toddlers in Pengodua Village, East Rote District, Rote Ndao Regency. The study used a qualitative approach with descriptive methods. The research informants numbered 16 people consisting of village officials, village midwives, integrated health post (Posyandu) cadres, mothers of toddlers, and pregnant women selected using a purposive sampling technique. Data were obtained through in-depth interviews, observation, and documentation, then analyzed using an interactive model that includes data reduction, data presentation, and drawing conclusions. The results showed that the implementation of the PMT Program has been carried out through four main aspects: processing supplementary food based on local foods, providing supplementary food to target toddlers, nutrition counseling to parents of toddlers, and recording program implementation. Food processing has taken into account the use of local foods and hygiene principles, while PMT distribution is carried out according to a predetermined schedule. Nutrition counseling has provided additional knowledge to some parents, but its implementation remains limited, resulting in uneven coverage of all targets. Program records have been maintained for monitoring, although several administrative challenges and limited community participation remain. Overall, the implementation of the PMT Program in Pengodua Village has been quite successful, but improvements are needed in terms of target distribution, the intensity of counseling, and strengthening coordination between implementers to optimally achieve the goals of improving toddler nutritional status and preventing stunting.